Factores personales e institucionales relacionados a la calidad de las anotaciones de enfermería en el servicio de cirugía del Hospital Guillermo Almenara Irigoyen, abril-junio, 2011 - Bartolo Estrella, Carmen Rosa (2019)
Objective: The overall objective of the research was to determine the level of knowledge, attitudes and practices ofthe bioethical principles of professional nursing in patient care in the surgery department. Methodology: This studyis a quantitative approach, non-experimental design and scope exploratory, descriptive. The population consistedof nurses working in the health care area of General Surgery which represent a total of 20 nurses; it is considered100% of the population. Data were collected using three instruments: a multiple choice questionnaire to measure thelevel of knowledge, the scale type Likerth to measure the attitudes and an observation guide for measuring the levelof practice. Results: The 60% of nurses have a good level of knowledge, while only 15% an outstanding level ofknowledge. Also, about the level of attitude, 80% of nurses has a level of positive attitude. In the level of practice,60% of the population put in practice all bioethical principles during patient care, collaborating on improving thequality life of the patient as far as possible giving excellent physical care, mental and spiritual. Conclusion: Thereis a significant correlation between the level of knowledge and practice (r = 0.526, p valor 0.017). The interactionbetween knowledge, attitudes and practices, are expressed in health are among social settings, and contribute to thetechnical, scientific and humanistic development of the profession.